Attraction and Retention—Maine’s Challenge - Cervone, Ed (Maine Policy Review, 2012)
In the Margaret Chase Smith Essay Ed Cervone, Presdent/CEO of the Maine Development Foundation, discusses Maine’s demographic challenges in attracting and retaining population if the state is to grow its economy and sustain that growth. He makes recommendations for attracting a larger, younger, and more diverse population.
Keywords: Maine demographics; attraction and retention; economic development; labor force